Comparison of visibility threshold on different chromatic contrast objects / Saiful Azlan Rosli … [et al.] - Rosli, Saiful Azlan; Aladin, Anis Zahirah; Muhamad, Nurulain; Chen, Ai-Hong (Penerbit UiTM (UiTM Press), 2016)
The aim of this study was to compare the visibility threshold of eight plates with different chromatic contrast. The staircasepsychophysics method based on the resolution of gaps in Landolt C was used to determine the average visibility threshold. Thirty young adults with best-corrected visual acuity of 6/6, normal colour perception and no history of ocular diseases were recruited. The results showed a combination of white on blue background plate gave a highest visibility level (mean=44.48±6.37m), while red on a blue background was the least visible combination (mean=33.30±4.68m). In conclusion, the chromatic contrast of an object can affect the visibility threshold.